Correlation between screen time and physical activity to student's physical fitness - Prakoso, Anang Bagus; Arief, Nur Ahmad; Muin, Abd; Wardani, Nurul Kusuma (Universitas Negeri Yogyakarta, 2024)
The development of electronic media may increase screen time (ST) duration, cause students to develop sedentary habits, and decrease their physical activity (PA). Lately, this has been thought to be the cause of the problem of low physical fitness (PF) among students. This study aimed to analyze the correlation between screen time, physical activity, and students' physical fitness. The design of this study was correlational, with a total of 88 subjects in grades 4 and 5 at Primary Laboratoy School (Labschool) Unesa 1. The sampling technique was simple random sampling. Nusantara students' physical fitness test (TKPN) was employed to assessed physical fitness, screen time-based sedentary behaviour questionnaire to assessed sedentary behaviour, and physical activity questionnaires for older children to assessed physical activity level. Data were collected in alignment with the physical education schedule for each class. Multinomial logistic regression was employed for data analysis. Findings revealed a significant simultaneous correlation among sedentary time (ST), physical activity (PA), and physical fitness (PF) (p = 0.017). However, partial analysis indicated no significant correlation between ST and PF (p = 0.517), while PA demonstrated a significant correlation with PF (p = 0.013). The results of the descriptive analysis showed that 73.9% of participants had very poor levels of physical fitness, and 43.18% of participants had low physical activity levels, with an average daily screen time duration of 3.03 hours. Participants accessed electronic media mostly to play games on smartphones, with an average of 2.28 hours. This study concluded that screen time was not directly affecting physical fitness but could reduce physical activity and student fitness. Despite screen time having no direct impact on physical fitness, this study recommends continuing to monitor screen time duration and increasing physical activity levels to mitigate potential risks associated with excessive screen use.